Long-term survival with anlotinib as a front-line treatment in an elderly NSCLC patient: A case report - Wang, Jingyi; Li, Xiaoqing; Zhou, Juan; Qiu, Dan; Zhang, Mengyao; Sun, Lan; Li, Shengwen Calvin (Frontiers in Oncology, 2023)
Background Half of the population of non-small cell lung cancer (NSCLC) patients are older than 70 years and have limited therapeutic options due to poor tolerance and being excluded in most clinical trials. Anlotinib hydrochloride, a novel oral multi-target tyrosine kinase inhibitor, has been approved for the standard third-line treatment for NSCLC in China. Herein we report an elderly NSCLC patient without any driver gene mutations who was undergoing anlotinib as a front-line treatment and who achieved long-term survival. Case summary The 77-year-old male patient was admitted to the hospital for chest tightness after engaging in physical activity for a week. The patient has been diagnosed with stage IIIB driver gene-negative squamous cell lung carcinoma. After that, he was treated with anlotinib for 2 years and 10 months from the first diagnosis until the last disease progression. Briefly, anlotinib combined with platinum-based chemotherapy was performed as the first-line therapy over six cycles. After 6 more cycles of anlotinib monotherapy maintenance, disease progression occurred. Then, anlotinib combined with tegafur was administered as a salvage treatment, and the disease was controlled again. After 29 cycles of anlotinib combined with tegafur regimens, the disease progressed finally. The patient achieved a total of 34 months of progression-free survival after anlotinib was used as the front-line treatment. He is still alive with a good performance status now (performance status score: 1). Conclusion This patient achieved long-term survival using anlotinib as a front-line regimen combined with chemotherapy.